ASSESSMENT OF AWARENESS OF TYMBARK’S PROMOTIONAL ACTIVITIES - Elżbieta Jurczuk; Anna Grontkowska (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2018)
The aim of the study is to determine the awareness of Tymbark's promotional activities. The researchwas carried out using a questionnaire on a sample of 120 respondents (30 by PAPI and 90 CAWI ). Theresearch shows that Tymbark is a well-known and recognizable brand on the Polish market. Creativemarketing activities, such us innovative product packages and unconventional promotion were, moreeffective than traditional marketing.